2013
DOI: 10.2991/itmr.2013.3.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research Areas and Grand Challenges in Electronic Medical Record: A Literature Survey Approach

Abstract: This study undertook a literature survey to provide a taxonomy that represents research areas of Electronic Medical Record (EMR). We identified the following areas of research and classified them into eight main categories: design and implementation, evaluation, adoption, impacts, medical research, integration, EMR data design and management, and policy and standards. Even though EMR improves care quality and efficiency in a positive way, some negative perceptions by the health user community (health professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…To conduct this literature survey, we followed the guidelines used by previous literature (Najaftorkaman et al, 2013), including three main discrete activities: (i) searching the initial list of papers; (ii) appraising relevant papers; (iii) extracting and analysing data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To conduct this literature survey, we followed the guidelines used by previous literature (Najaftorkaman et al, 2013), including three main discrete activities: (i) searching the initial list of papers; (ii) appraising relevant papers; (iii) extracting and analysing data.…”
Section: Methodsmentioning
confidence: 99%
“…We identified initial search resources informed through prior work (Najaftorkaman et al, 2013). We considered that the relevant papers might distribute in the areas of research in Information and Computing Sciences, Biomedical Engineering, and Medicine and Health Sciences.…”
Section: Initial Searchmentioning
confidence: 99%
“…A study from Afghanistan, conducted in hospitals in two different regions, found that readiness differed significantly between the hospitals included in the study due to the extent of usage of the technologies by providers [25]. A number of studies stressed the importance of assessing healthcare provider readiness for the implementation of ICTs in healthcare institutions [26, 27]. In Pakistan, stakeholders agreed that assessing readiness was essential to successful implementation [26].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Department of Trade and Industry (DTI) in the UK, Condition Based Maintenance (CBM) in wind turbine rotating elements has contributed to a saving of up to £1.3 billion per year [1]. Hence, Condition Monitoring (CM) of bearings has become a popular approach to increase performance and reduce costs [2][3][4].…”
Section: Introductionmentioning
confidence: 99%